Renal denervation for treatment of ventricular arrhythmias: data from an International Multicenter Registry - Ukena, Christian; Scholz, Eberhard P.; Thomas, Dierk (Clinical research in cardiology, 2016)
IntroductionVentricular arrhythmias (VAs) in patients with chronic heart failure (CHF) are sometimes refractory to antiarrhythmic drugs and cardiac ablation. This study aimed to investigate catheter-based renal sympathetic denervation (RDN) as antiarrhythmic strategy in refractory VA.MethodsThese are the first data from a pooled analysis of 13 cases from five large international centers (age 59.2 ± 14.4 years, all male) with CHF (ejection fraction 25.8 ± 10.1 %, NYHA class 2.6 ± 1) presented with refractory VA who underwent RDN. Ventricular arrhythmias, ICD therapies, clinical status, and blood pressure (BP) were evaluated before and 1-12 months after RDN.ResultsWithin 4 weeks prior RDN, a median of 21 (interquartile range 10-30) ventricular tachycardia (VT) or fibrillation (VF) episodes occurred despite antiarrhythmic drugs and prior cardiac ablation. RDN was performed bilaterally with a total number of 12.5 ± 3.5 ablations and without peri-procedural complications. One and 3 months after RDN, VT/VF episodes were reduced to 2 (0-7) (p = 0.004) and 0 (p = 0.006), respectively. Four (31 %) and 11 (85 %) patients of these 13 patients were free from VA at 1 and 3 months. Although BP was low at baseline (116 ± 18/73 ± 13 mmHg), no significant changes of BP or NYHA class were observed after RDN. During follow-up, three patients died from non-rhythm-related causes.ConclusionsIn patients with CHF and refractory VA, RDN appears to be safe concerning peri-procedural complications and blood pressure changes, and is associated with a reduced arrhythmic burden.
Gesehen am 29.11.2017